Mapping risk factors for substance use: Introducing the YouthMap12. (February 2017) - Pedersen, Mads Uffe; Rømer Thomsen, Kristine; Pedersen, Michael Mulbjerg; Hesse, Morten
Abstract: Background: In adolescence, psychological problems and regular use of alcohol, cigarettes, cannabis and other drugs (AOD) tend to cluster together, strongly indicating that certain groups of young people are at elevated risk of developing a problematic use of AOD. Objective: The aim of the present study was to develop an easy-to-implement screening instrument to identify subgroups of young people with different psychological problems at risk of problem use of AOD. Method: 3589 randomly selected young Danes between 15 and 25 years of age, from a national survey ( n = 2702) and a municipality survey ( n = 887), answered a 12-item questionnaire (YouthMap12) with 6 items identifying externalizing problems (EP6) and 6 items identifying internalizing problems (IP6). Latent class analysis (LCA) was used to characterize groups at risk, and associations were estimated between EP6 and IP6 and regular use of AOD, and between latent class membership and regular use of AOD. Results: LCA identified 6 classes with varying degrees of externalizing and internalizing problems: 70% of youth were in the low problem score class, and the remaining 30% were at various levels of risk. Regular use of cigarettes, cannabis and alcohol was strongly associated with classes characterized by externalizing problems, while over-the-counter and prescription medicine was strongly associated with classes characterized by internalizing problems. Conclusions: Youth at risk of problem use of AOD can be identified using a simple and easily administered instrument. Highlights: An "easy-to-implement" method to identify different risk groups was developed 1 low, 2 moderate and 3 high risk latent classes were identified in a national survey Externalizing problems were linked to cannabis, alcohol and cigarette use Internalizing problems were linked to use of OTC and prescription medicine The method was repeated in a municipality survey and findings were replicated